PENGARUH IQ, EQ, OCB , DAN SQ TERHADAP KINERJA PADA CIVITAS AKADEMIKA STIE ASIA MALANG - Wardani, Wiwit Setyo; Utami, Nunung Nurastuti (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2020)
Developments in the current era require companies to continue to develop and make appropriate strategic decisions. One strategic decision that must be appropriate is related to human resource development. One of the management developments is the management of human resources. One of them is in terms of intellectual intelligence, emotional intelligence, organizational citizenship behavior and spiritual intelligence on performance. This study aims to determine the effect of variables of intellectual intelligence, emotional intelligence, organizational citizenship behavior and spiritual intelligence on employee performance at the STIE ASIA Malang academic community. This study uses multiple linear regression analysis methods, validity test, reliability test, classic assumption test, and hypothesis testing and causal associative research types. Data collection using a questionnaire / questionnaire. The population in this study were all academics of STIE ASIA Malang and sampling techniques using 77 sample respondents. The results showed that: 1) intellectual intelligence influences performance 2) emotional intelligence influences performance 3) spiritual intelligence influences performance 4) organizational citizenship behavior (OCB) influences performance.